Forecasting development of road technology based on the Delphi method – selected issues - Radziszewski, Piotr; Nazarko, Joanicjusz; Król, Jan; Kowalski, Karol; Sarnowski, Michał (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
An objective of this research project is an analysis of development directions of new materials, technologies and pavement structures used in road industry, taking into account special environmental conditions and sustainable development rules. Results of the first round of conducted study based on the foresight method are described in this paper. Such results are helpful to provide support for making a long term strategy decisions by the government. Selected results and analysis in the scope of identification of the main research areas and hypothesis connected with developments of road technology are shown in this paper with a special focus on the construction of the durable pavements. It was found that the most important task is related to developments of the asphalt and cement pavements technology providing at least 30 years durability period. The construction of such pavements is possible only when high quality of work is provided and there is further road technology development as a result of the science and industry cooperation.